Розвиток сучасних методів дослідження складних соціально-економічних систем - Ромашко, Тетяна Володимирівна; Мазник, Ліана Валеріївна (My University, 2013)
The predictors of systemic approach as a new direction scientific methodology are defined in the article, the generalization of existing approaches to defining such categories as «system», «systems approach», «system analysis» is done, the methods of systematic analysis and scopes of their application are reviewed, the improved classification of systems is proposed.
Keywords: кафедра економіки праці та менеджменту; systematic analysis; system; systematic approach; системний підхід; систематичний аналіз; система